Bacillus thuringiensis RZ2MS9, a tropical plant growth‐promoting rhizobacterium, colonizes maize endophytically and alters the plant's production of volatile organic compounds during co‐inoculation with Azospirillum brasilense Ab‐V5. Issue 6 (25th August 2021) - de Almeida, Jaqueline Raquel; Bonatelli, Maria Letícia; Batista, Bruna Durante; Teixeira‐Silva, Natalia Sousa; Mondin, Mateus; dos Santos, Rafaela Cristina; Bento, José Maurício Simões; de Almeida Hayashibara, Carolina Alessandra; Azevedo, João Lúcio; Quecine, Maria Carolina
Summary: The beneficial features of Bacillus thuringiensis ( Bt ) are not limited to its role as an insecticide; it is also able to promote plant growth interacting with plants and other plant growth‐promoting rhizobacterium (PGPR). The PGPR Bt strain RZ2MS9 is a multi‐trait maize growth promoter. We obtained a stable mutant of RZ2MS9 labelled with green fluorescent protein (RZ2MS9‐GFP). We demonstrated that the Bt RZ2MS9‐GFP successfully colonizes maize's roots and leaves endophytically. We evaluated whether RZ2MS9 has an additive effect on plant growth promotion when co‐inoculated with Azospirillum brasilense Ab‐V5. The two strains combined enhanced maize's roots and shoots dry weight around 50% and 80%, respectively, when compared to the non‐inoculated control. However, non‐differences were observed comparing RZ2MS9 alone and when co‐inoculated with Ab‐V5, In addition, we used co‐inoculation experiments in glass chambers to analyse the plant's volatile organic compounds (VOCs) production during the maize‐RZ2MS9 and maize‐RZ2MS9‐Ab‐V5 interaction. We found that the single and co‐inoculation altered maize's VOCs emission profile, with an increase in the production of indoles in the co‐inoculation. Collectively, these results increase our knowledge about the interaction between the Bt and maize, and provide a new possibility of combined application with the commercial inoculant A. brasilense Ab‐V5.